Effect of Honey Type on Chemical and Sensory Quality of Kratom Herbal Tea (Mitragyna speciosa) - Juwitaningsih, Dayang Dwi; Priyono, Suko; Saputri, Nur Endah (Journal of Health and Nutrition Research, 2024)
Indonesia has a lot of large forests with a diversity of plant species. That diversity of plants can potentially be used as medicinal plants. Indonesians have long identified many plants with medicinal benefits as an effort to overcome various health problems, one of the plant is the kratom (Mitragyna speciosa). Kratom leaves are consumed as tea by brewing it with hot water. Some Kapuas Hulu people use sweeteners such as honey, to reduce the bitterness of kratom. The mixture of kratom herbal tea added with sweet honey is expected to produce sensory and functional attribute which will affect consumers in choosing products. This experiment used a Randomized Block Design (RBD). Statistical analysis of research data using ANOVA (Analysis of Variance) test with a rate of 5%. The results of the sensory research of kratom herbal tea showed a significant effect on taste, but no significant effect on aroma and color, namely the color value of 2.08, aroma 2.28 and taste 2.25. The addition of honey variations to kratom herbal tea included vitamin C, flavonoids, alkaloids, and antioxidants, which was vitamin C content ranges from 8.9-13.5 mg/100 g, flavonoids 15.2-27.56 mg QE/ml, alkaloids 53.1-55.4% and antioxidant activity 39.1-80.1%.